Community Composition Of Top Soil Collembola In The Land Application Area Of Liquid Waste Oil Palm Plantation Factory Simpang Kanan District Rokan Hilir Regency (International Journal of Ecophysiology, 2022)
This research has been conducted to knowing and analyze the community composition of top soil Collembola in the land application area oil palm plantation at Simpang Kanan District, Rokan Hilir  Regency.  Sampling  Area  Assessed  Through â€œPurposive Random Samplingâ€  in which top soil Collembola which were collected by using Pitfall Trap. Location of sampling area through at three location. The first location at block 1 as control, the second location at block 2 which by using land application Flatbed system, and the third location at block 3 which by using land application longbed system. There were fourteen species of Collembola classified into three families and one order. The highest value of  species compotition at first location as control was Entomobrya sp.1 amount 27.907 %. The second location (Block 2) which by using Flatbed system the highest value of  species compotition was Entomobrya sp.3 amount 35.439%. The third  location  (Block  3)  which  by  using  Longbed  system,  the  highest  value  of    species compotition was Entomobrya sp.1  amount 27.076 %.